Increased expression of upstream TH2-cytokines in a mouse model of viral-induced asthma exacerbation. Issue 1 (December 2016) - Mahmutovic Persson, Irma; Akbarshahi, Hamid; Menzel, Mandy; Brandelius, Angelica; Uller, Lena
Abstract Background Exacerbations of asthma caused by respiratory viral infections are serious conditions in need of novel treatment. To this end animal models of asthma exacerbations are warranted. We have shown that dsRNA challenges or rhinoviral infection produce exacerbation effects in mice with ovalbumin (OVA)-induced allergic asthma. However, house dust mite (HDM) is a more human asthma-relevant allergen than OVA. We thus hypothesised that dsRNA challenges in mice with HDM-induced experimental asthma would produce important translational features of asthma exacerbations. Method Mouse airways were challenged locally with HDM or saline three times a week for three weeks to establish experimental asthma. Then daily local dsRNA challenges were given for three consecutive days to induce exacerbation. Bronchoalveolar lavage fluid (BALF) was analysed for inflammatory cells, total protein, the necrosis marker LDH and the alarmin ATP. Lung homogenates were analysed for mRNA expression (RT-qPCR) of TNF-α, CCL2, CCL5, IL-1β, IL-33, thymic stromal lymphopoietin (TSLP), and IL-25 as well as pattern recognition receptors (PRRs) RIG-I, MDA5 and TLR3. Lung tissue IL-33 was analysed with ELISA and PRRs were quantified by western blot. Immunohistochemistry indicated lung distribution of IL-33. Results HDM challenge alone caused sustained increase in BALF total protein, eosinophils, lymphocytes and neutrophils, and transient increase in lung tissue expression of TSLP, IL-33 and TNF-α. dsRNA-induced exacerbation markedly and dose-dependently exaggerated these effects. Further, BALF levels of LDH and ATP, and lung tissue expression of CCL2, CCL5, IL-1β, IL-25 and PRRs were increased exclusively at the exacerbations. Lung protein levels of IL-33 were transiently increased by HDM and further increased at exacerbation. Conclusion We demonstrate several novel aspects of HDM-induced experimental asthma and added exacerbation effects of dsRNA. General inflammatory parameters in BALF such as exuded proteins, mixed granulocytes, LDH and ATP were increased at the present exacerbations as they are in human asthma exacerbations. We suggest that this model of asthma exacerbation involving dsRNA challenges given to mice with established HDM-induced asthma has translational value and suggest that it may be particularly suited for in vivo studies involving pharmacological effects on exacerbation-induced expression of major upstream TH2 -cytokines; IL-33, TSLP and IL-25, as well as PRRs.